Clinical education : exploring digital tools, multi-source feedback, and formative assessment for nursing student learning in EMS - Tomas Nilsson (2025)
IntroductionClinical education is a cornerstone of undergraduate nursing programs, traditionally situated in hospitals and other care facilities. However, the rising demand for placements highlights the need for alternative learning environments. The Emergency Medical Services (EMS) represents an underutilized, but valuable context that exposes undergraduate nursing students (UNS) to diverse patient encounters, fosters interprofessional collaboration, and strengthens rapid decision-making skills in unpredictable situations. Despite its potential, assessing UNS in EMS is complex due to brief patient interactions, multiple supervisors, and dynamic clinical conditions. Traditional assessment instruments, developed for hospital context, may not capture the unique competencies required in EMS, such as adaptability, rapid clinical reasoning, and teamwork. Moreover, reliance on summative assessments can limit opportunities for ongoing learning. Consequently, there is a need to explore innovative feedback approaches that supports formative assessment, promote objectivity, and ensure alignment with intended learning outcomes (LO`s) and national curriculum standards. This thesis addresses this gap through three studies exploring UNS learning experiences and assessment processes during clinical education in the EMS, focusing on the use of digital assessment tool (DAT) and Multi-source feedback (MSF) to enhance formative and assessment.MethodsA mixed-methods approach was employed in study I were 50 clinical supervisors assessed four simulated scenarios using two different instruments with similar LOs, followed by 28 qualitative interviews. Quantitative data were analysed using descriptive statistics and logistic regression, while qualitative data were analysed using thematic analysis. Study II used a qualitative design, with group interviews including 16 UNS and individual interviews including 13 supervisors, focusing on their experiences using a DAT in EMS for formative feedback purposes. Data were analysed using Graneheim and Landman’s method for content analysis. Study III adopted a qualitative, inductive approach, conducting four focus group interviews with 31 final-semester UNS who received MSF facilitated by a digital tool during EMS placements. Data were analysed using reflexive thematic analysis according to Braun and Clark.ResultsStudy I demonstrated that while the two assessment instruments produced equivalent pass/fail outcomes, supervisors reported challenges with subjectivity, ambiguous phrasing of LOs, and inconsistent grading scales. These factors contributed to arbitrary judgments, limited day-to-day use, and difficulties in providing formative feedback. Supervisors emphasized the potential of team-based assessments and repeated evaluations to improve validity.Study II found that both UNS and supervisors experienced DAT as supportive of learning, reflection, and transparency. The Likert scale enabled visualization of progress, and the digital format facilitated communication compared to traditional paper-based methods. UNS valued its clarity and structure, while supervisors noted improved opportunities for formative feedback. However, participants requested greater integration with university systems and stronger links to course objectives.Study III highlighted UNS positive experiences with MSF in EMS. Feedback from supervisors and peers fostered self-awareness, professional growth, and reflective practice, while input from patients and health care professionals provided diverse perspectives despite contextual and logistical challenges. UNS appreciated the breadth of insights offered through MSF but stressed the need for structured implementation and digital support to ensure relevance and manage workload constraints.ConclusionThis thesis demonstrates that assessment in EMS requires approaches that extend beyond traditional summative instruments and adapt to the unique challenges of the prehospital environment. While existing tools may yield consistent grading outcomes, their formative value is limited by subjectivity, unclear definitions, and contextual constraints. The findings show that DAT can enhance transparency, structure, and communication, offering UNS clearer insight into their learning progress. Similarly, MSF enriches professional development by incorporating diverse perspectives, fostering self-reflection, and supporting collaborative learning, although patient and interprofessional input can be challenging to obtain. Supervisors emphasized the potential of team-based approaches to mitigate subjectivity and strengthen validity, highlighting the importance of structured support in the assessment process. Collectively, the three studies underscore the need for innovative, context-sensitive feedback frameworks that align with curriculum standards while capturing competencies central to EMS practice, such as adaptability, rapid clinical reasoning, and teamwork. By integrating DAT and MSF into EMS education, clinical placements can evolve into structured, high-quality learning environments that not only enhance formative assessment but also prepare UNS for safe, effective, and patientcentred care.List of scientific papersI. Tomas N, Italo M, Eva B, Veronica L. Assessment during clinical education among nursing students using two different assessment instruments. BMC Med Educ. 2024;24(1):852. https://doi.org/10.1186/s12909-024-05771-xII. Nilsson T, Masiello I, Broberger E, Lindström V. Digital feedback during clinical education in the emergency medical services: a qualitative study. BMC Med Educ. 2023 Mar 14;23(1):156. https://doi.org/10.1186/s12909-023-04138-yIII. Nilsson T, Masiello I, Broberger E, Lindström V. Clinical education: nursing students' experiences with multisource feedback using a digital assessment instrument in the emergency medical service - a qualitative study. BMC Med Educ. 2025;25(1):391. https://doi.org/10.1186/s12909-025-06950-0